Evaluasi Usability dan Rekomendasi Perbaikan pada Aplikasi E-Kinerja Kabupaten Kediri menggunakan Metode Heuristic Evaluation - Narayana Demafaris Pradana; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
E-Kinerja of Kediri Regency is an E-Government information system application that can record and report the performance of Kediri Regency Government employees. Based on interviews with application users, there are several usability issues faced by users. Usability issues can reduce user productivity in using the application. Therefore, an evaluation to find and solve usability issues in a user interface is needed. Heuristic Evaluation is a method of usability evaluation that involves experts as evaluators to assess elements at an interface based on the heuristic usability principle. The heuristic usability principle used by evaluators in this study is nine principles proposed by Monroy. The evaluators assess the severity rating of each usability issues with a scale value of 1-5. The evaluation was carried out in three stages, i.e. the first evaluation, recommendation for improvement (making recommendations, designing a wireframe, and making a high-fidelity prototype design), and the second evaluation. The first evaluation and the second evaluation were conducted by the same three evaluators. The first evaluation provides 23 usability issues while the second evaluation provides two usability issues that consists of two new usability issues and three old usability issues that still exist.